Lack of proper defence and international judicial cooperation. Pathologies in the service of judicial documents between Spain and Switzerland - Lana Arceiz, Víctor Javier (CUADERNOS DE DERECHO TRANSNACIONAL, 2023)
Among the tools for international judicial cooperation, the service of judicial documents has a highlighted importance due to their link to the due process, while its regulations aim to accelerate the communication system. The 1965 Hague Convention is among the frequently applied rules, together with those of European origin, in the cross-border service of judicial documents. In the present work, a case of notification of a claim under said tool is analysed, in which the State of destination is Switzerland. The interest lies in the fact that the summons was carried out in contravention of the reservations made by the said country: it was carried out by direct post mail and without providing the German translations of the documents. Such a circumstance could give rise to lack of proper defence of the defendant in Spain, compromising his defence rights, which could open the door to an eventual annulment of proceedings.
Keywords: international judicial cooperation; service of judicial documents abroad; 1965 Hague Convention; lack of proper defence